Bridging The Digital Divide: Financial and Ethical Challenges - Oddo, Alfonso R. (Teaching business ethics, 2002)
The digital divide – the widening gapbetween people who can use computers and theInternet to advance themselves, and those who,because of poverty, education, or otherbarriers, cannot – offers some unique financialand ethical challenges. Fallows (2000), inThe Invisible Poor, reports on the stateof the U.S. economy as it affects the poor. Among other issues, Fallows argues thateconomic growth separates the classes, ratherthan bringing them together. Attali (2000)suggests a possible solution to this economicgap. Attali believes that “...the only concreteway to reduce the poverty gap is within thecontext of free market economy. It can be doneby combining the two success stories of thelast decade: entrepreneurship and technology,more specifically: microfinance and theInternet.” This article addresses some issues related tohow technology, particularly in the area offinancial services, has affected the ability ofthe poor to better themselves. Ethicalchallenges that accompany Information Agepoverty are examined in the context of effortsto narrow the digital divide.